2022
DOI: 10.3390/f13060834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of a Combined Chemical and Thermal Modification of Wood though the Use of Bicine and Tricine

Abstract: The effects of thermal modification of wood have been well established, particularly in terms of reductions in mechanical performance. In recent years, there has been an increase in studies related to the Maillard reaction. More commonly associated with food chemistry, it involves the reaction of amines and reducing sugars during cooking procedures. This study has attempted to combine the use of amines and thermal modification, with subsequent properties investigated for the treatment of spruce (Picea abies (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This was studied in more detail by Peeters et al (2018). The potential of tricine as a potential treatment was explored further (Jones et al, 2019), whereby wood samples were treated with tricine and bicine respectively before thermal modification at a slightly reduced temperature (160 o C), due to the potential of thermal degradation of the chemicals at temperatures above 180 o C. This combined modification resulted in a slight limitation of mechanical property losses, whilst evaluation of colour data seemed to suggest there was an effect from the inclusion of the amine compounds resulting in a Maillard-type reaction. Additional studies by Fourier transform Infra-red (FTIR) spectroscopy (Popescu et al, 2020) confirmed the reaction had occurred to some extent.…”
Section: Fig 2: European Distribution Of Termite Species (Courtesy Of...mentioning
confidence: 99%
“…This was studied in more detail by Peeters et al (2018). The potential of tricine as a potential treatment was explored further (Jones et al, 2019), whereby wood samples were treated with tricine and bicine respectively before thermal modification at a slightly reduced temperature (160 o C), due to the potential of thermal degradation of the chemicals at temperatures above 180 o C. This combined modification resulted in a slight limitation of mechanical property losses, whilst evaluation of colour data seemed to suggest there was an effect from the inclusion of the amine compounds resulting in a Maillard-type reaction. Additional studies by Fourier transform Infra-red (FTIR) spectroscopy (Popescu et al, 2020) confirmed the reaction had occurred to some extent.…”
Section: Fig 2: European Distribution Of Termite Species (Courtesy Of...mentioning
confidence: 99%
“…The initial spacing between trees cultivated in a location, intercropping with a variety of indigenous plants, drying procedures to decrease moisture contents in wood [4], growing season, extractive content, and the moisture content and hygroscopicity of wood [5,6] are among the myriad factors that affect the size and dimension of cells in wood species, eventually resulting in a wide variance between solid wood species, and even within the same wood species grown in different localities. Moreover, weathering and environmental impacts on wood can also be of great importance, as they affect many wood properties, including the appearance, service life, performance of different coatings and finishes, and also their comparison [7][8][9]. As such, these external factors also greatly affect the preservation and conservation of heritage objects that should be maintained and preserved for future generations [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In another interesting study, an attempt was made to combine the use of chemical treatments by amines (tricine and bicine) and thermal modification to investigate the properties of the treated spruce and beech wood [7]. However, an improvement of the properties of wood by such combining treatment was not confirmed in these studies.…”
mentioning
confidence: 99%